SEMIGRUP REGULER DAN SIFAT-SIFATNYA - Najmah Istikaanah; Ari Wardayani; Renny Renny; Ambar Sari Nurahmadhani; Agustini Tripena Br. Sb.; Triyani Triyani (Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2021)
This article discusses some properties of regular semigroups. These properties are especially concerned with the relation of the regular semigroups to ideals, subsemigroups, groups, idempoten semigroups and invers semigroups. In addition, this paper also discusses the Cartesian product of two regular semigroups. Keywords:ideal, idempoten semigroup, inverse semigroup, regular semigroup, subsemigroup.